2018
DOI: 10.1186/s40168-018-0400-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predation stress and food ration on perch gut microbiota

Abstract: BackgroundGut microbiota provide functions of importance to influence hosts’ food digestion, metabolism, and protection against pathogens. Factors that affect the composition and functions of gut microbial communities are well studied in humans and other animals; however, we have limited knowledge of how natural food web factors such as stress from predators and food resource rations could affect hosts’ gut microbiota and how it interacts with host sex. In this study, we designed a two-factorial experiment exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 68 publications
2
71
0
Order By: Relevance
“…The prevalence of invasion of Proteocephalus sp. in perch from Chany Lake was 12.7% that correlates with early investigations where it was shown that prevalence of infestation of P. cernuae in perch from Chany Lake was 13.2% (Sous and Rostovsev 2006 (Li et al, 2014;Silva et al, 2011;Ye, Amberg, Chapman, Gaikowski, & Liu, 2014;Baldo, Riera, Tooming-Klunderud, Albà, & Salzburger, 2015;Kashinskaya et al, 2015;Liu et al, 2016;Zha, Eiler, Johansson, & Svanbäck, 2018).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The prevalence of invasion of Proteocephalus sp. in perch from Chany Lake was 12.7% that correlates with early investigations where it was shown that prevalence of infestation of P. cernuae in perch from Chany Lake was 13.2% (Sous and Rostovsev 2006 (Li et al, 2014;Silva et al, 2011;Ye, Amberg, Chapman, Gaikowski, & Liu, 2014;Baldo, Riera, Tooming-Klunderud, Albà, & Salzburger, 2015;Kashinskaya et al, 2015;Liu et al, 2016;Zha, Eiler, Johansson, & Svanbäck, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…By comparing data on bacterial diversity in perch gut with microbiota data from other fish, we can conclude that the microbial composition at the phylum level in the perch intestine conforms to the available literature. Thus, the dominant microbiota in the intestine of freshwater fish was represented by Proteobacteria, Firmicutes, Bacteroidetes, Fusobacteria, Tenericutes and Fusobacteria (Li et al, ; Silva et al, ; Ye, Amberg, Chapman, Gaikowski, & Liu, ; Baldo, Riera, Tooming‐Klunderud, Albà, & Salzburger, ; Kashinskaya et al, ; Liu et al, ; Zha, Eiler, Johansson, & Svanbäck, ). Other metagenomic studies have shown that the microbiota of the perch P. fluviatilis was dominated by the phyla Tenericutes, Proteobacteria, Fusobacteria and Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disruption of the microbiome is likely to represent an important mechanism by which stress affects fish health, welfare and performance in aquaculture. There is some evidence that environmental and social stressors disrupt microbial communities associated with the fish gut and skin (Boutin et al 2013; Sylvain et al 2016; Uren Webster et al 2019; Zha et al 2018), however, a potential role of cortisol in mediating these effects is unknown. We hypothesised that stress-induced cortisol production would directly disrupt the fish microbiome.…”
Section: Introductionmentioning
confidence: 99%